The Suspect Restitutionary Basis for Common Benefit Fee Awards in Multi-District Litigations - Silver, Charles (Texas law review, 2023)
MDL judges cling to this rationale firmly.10 With the singular exception of Judge Vince Chhabria, whose thoughtful opinion in In re Roundup Products Liability Litigation11 may mark a turning point, MDL judges appear to consider it settled law.12 But it is not and never could be-first and foremost because it is doctrinally incoherent. The Common Fund Doctrine Discussions of the common fund doctrine typically start with Trustees v. Greenough,21 a case whose paradigm facts nicely frame the purpose and limits of the equitable doctrine. 22 The restitution claimant in Greenough was a holder of bonds secured by a trust indenture. In such a case there is no question of imposing a liability for unrequested benefits that should have been the subject of contract-benefits that the recipient should have had a chance to refuse.26 Recovery from a fund that was already under the supervision of the court guaranteed that no beneficiary would be required to make an expenditure; the courts merely applied the usual rule that a trust bears the expense of its own administration. "33 It also noted with approval that the district court's order imposing an 8% tax on lawyers' contingent fees applied to all IRPAs "except those attorneys who had actively participated in the pre-trial activities," which